The Role of PPAT in Making the Deed of Sale and Purchase and the Authorized to Sell Certified Land - Ilham Wahyu Wicaksana; Djunaedi Djunaedi; Andi Aina Ilmih (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to identify and analyze the role and authority of the Land Deed Making Official (PPAT) in making the deed of sale and purchase and the power of attorney to sell certified land rights and the obstacles and solutions faced by the Land Deed Making Official (PPAT) in making the deed of sale and purchase and deed of power of attorney to sell certified land rights. The use of the sociological juridical approach in legal research is due to the fact that the problems studied are closely related to juridical and sociological factors. The analytical knife in answering the problem formulation uses the theory of legal certainty and the theory of authority. The Role and Authority of the Land Deed Making Official (PPAT) in the making of the Sale and Purchase Deed (AJB) and the Authorized Deed to Sell Certified Land Rights in Rembang Regency, namely the Preparation of the Sale and Purchase Deed and the implementation of the AJB. In making the PPAT deed, the parties who carry out legal actions regarding Land Rights and Ownership Rights to Flat Units must be present before PPAT to convey the aims and objectives to PPAT. Obstacles faced by Land Deed Making Officials (PPAT) in making the Deed of Sale and Purchase and the Authorized Deed to Sell Certified Land Rights in Rembang Regency in the event of a default or unlawful act committed by one of the parties. The occurrence of these obstacles, then PPAT can provide solutions to the parties to deliberation first in resolving the problem.